2020
DOI: 10.22271/chemi.2020.v8.i6b.10757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar spray of plant growth regulators on growth of potted hibiscus

Abstract: Investigation was done to study the effect of foliar spray of plant growth regulators on growth and flowering of potted hibiscus plants grown in pot during 2017-18 and 2018-19. Application of gibberellic acid, benzyl adenine and salicylic acid at different concentrations found significant in influencing the vegetative growth, flowering parameters and plant pigments of Hibiscus rosa-sinensis plants during both the years as compared to untreated plants (control). Plants sprayed with 100 ppm gibberellic acid resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Patel et al [21] observed similar results in gerbera, with GA3 at 150 ppm resulting in the fewest days to first flower initiation (108.33 days), maximum flower diameter (8.76 cm), flower weight (5.93 g), and shelf life of flowers (8.00 days). GA3 also increased the number of suckers, and foliar application of 150 ppm GA3 was found to be the best for enhancing plant growth, yielding the maximum number of cut blooms with longer stalks and larger flower sizes, as reported by Sharifuzzaman et al [22] in chrysanthemum, Jamal et al [23] in gerbera and Sainath et al [24] in chrysanthemum observed similar earliness in the full opening of flowers due to GA3 treatments.…”
Section: Influence Of Plant Growth Regulators On Flowering Parametersmentioning
confidence: 56%
“…Patel et al [21] observed similar results in gerbera, with GA3 at 150 ppm resulting in the fewest days to first flower initiation (108.33 days), maximum flower diameter (8.76 cm), flower weight (5.93 g), and shelf life of flowers (8.00 days). GA3 also increased the number of suckers, and foliar application of 150 ppm GA3 was found to be the best for enhancing plant growth, yielding the maximum number of cut blooms with longer stalks and larger flower sizes, as reported by Sharifuzzaman et al [22] in chrysanthemum, Jamal et al [23] in gerbera and Sainath et al [24] in chrysanthemum observed similar earliness in the full opening of flowers due to GA3 treatments.…”
Section: Influence Of Plant Growth Regulators On Flowering Parametersmentioning
confidence: 56%